Pemikiran Filsafat Progresivisme John Dewey dalam Pendidikan - Maisy Afriliany; Siti Najla P; Umi Kalsum; Herlini Puspika Sari (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Education aims to help students become more independent and critical in the process of discovering their own identity. Participatory education is a relevant approach that allows students to actively participate in the thinking process. The philosophy of educational progressivism pioneered by John Dewey reflects much of this approach. According to progressivism, education should be student-centered by emphasizing hands-on experience to teach and build critical thinking skills. Relevant works on progressivism and Dewey's concept of education are investigated in this qualitative research. The results show that the idea of progressivism is strongly related to Indonesia's national education goal, which is to create innovative, independent, and flexible students. A student-centered curriculum and a supportive education system are needed to implement this theory.